ANALISIS PERHITUNGAN BIAYA PENGEMBANGAN PERANGKAT LUNAK PEMERINTAH: STUDI KASUS PADA PUSINTEK, KEMENTERIAN KEUANGAN - Ramdhany Achmad Noer Pare; Dyah Purwanti (SUBSTANSI, 2018)
This study aim to propose a software costing for public sector, by using both of activity-based costing (ABC) method and traditional costing method. We based on a case study in Pusintek, Ministry of Finance and using a field observation, interviews and literature studies to collect data and information such as related to the preparation of software costing simulations. Finally, we proposed a software costing by ABC method and traditional costing method for Pusintek. We find that the software costing by ABC is cheaper than traditional costing, however the ABC costing takes more assumption and more complex calculations. We have several limitation related to lack of data, use more assumptions and find a complicated of data’s segregation. We suggest to use traditional costing to calculate the software cost, because traditional costing is simpler and practicable in the public sector, since the degree of complexity is lower than ABC costing. The ABC has more accurate cost calculation, but it considers more assumption, need more documents, and higher complexity of job’s procedures. In the public sector, it was still a lack of requirement to apply the ABC.